Perbandingan Warna Tepung Suweg Fase Dorman dan Vegetatif Secara Instrumental dan Sensoris - Umar Hafidz Asy’ari Hasbullah; Rini Umiyati (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
The color of the flour has an important role because it will happen to the resulting derived product. This study was to compare the color of suweg flour produced from the dormant and vegetative phases in instrumental and sensory. Instruments using Chromameter. Parameters observed from L *, a *, b *, chroma, and hue degrees. Sensory testing uses a rank test of color preferences, brown color and color brightness. The results showed significant differences in L *, a *, b *, and chroma values between dormant and vegetative phase flours. The degree value of hue was not significantly different between the two treatments. Panellists stated 100% liked the color of the dormant flour stage than vegetative.Additionally, the color of the vegetative phase flour was assessed by more than 80% of the panelists claiming to be more brown and more than 90% of the panelists stated darker than dormant. Pearson correlation test results show that there are correlation in some parameter of instrument and sensory. Keywords: suweg flour, color, dormant, vegetative, chroma, hue